Performance evaluation and kinetic modeling of the start-up of a UASB reactor treating municipal wastewater at low temperature - Turkdogan-Aydinol, F. Ilter; Yetilmezsoy, Kaan; Comez, Sezen; Bayhan, Hurrem (SPRINGER, 2011)
A kinetic modeling-based study was carried out to evaluate the start-up performance of a 10-L up-flow anaerobic sludge blanket (UASB) reactor treating municipal wastewater under different organic and hydraulic loading conditions. The reactor was operated for 105 days (around 4 months) below 20 A degrees C and with three different hydraulic retention times of 24, 12 and 5 h. Imposed volumetric organic loading rates (OLR) ranged from 0.57 (+/- 0.05) to 11.78 (+/- 0.85) kg TCOD/m(3)-day. Although relatively high incoming volumetric OLR values were employed to the system, the UASB reactor demonstrated a favorable performance on the anaerobic treatability of municipal wastewater, and no process failure was recorded in the start-up stage. On the basis of experimental results, the modified Stover-Kincannon model was successfully applied to define the start-up kinetics with a very high value of the correlation coefficient (R = 0.9729). Maximum substrate utilization rate constant and saturation constant of the modified Stover-Kincannon model were determined as U (max) = 1.996 g/L-day and K (B) = 1.536 g/L-day, respectively.
Keywords: Municipal wastewater; Up-flow anaerobic sludge blanket; Start-up stage; Low temperature; Stover-Kincannon; ANAEROBIC TREATMENT; DOMESTIC SEWAGE; SLUDGE BLANKET; REMOVAL; ACID; EFFICIENCY; OPERATION; COD; Biotechnology & Applied Microbiology; Engineering